A Multicenter Study of 239 Patients Aged Over 70 Years With Diffuse Large B-Cell Lymphoma in China - Yang, Chunli; Li, Qiaoer; Xie, Ke; Zhang, Yakun; Xiang, Dania; Han, Yunwei; Zou, Liqun (Frontiers in Pharmacology, 2022)
Background Diffuse large B-cell lymphoma (DLBCL) is the most common aggressive lymphoma subtype worldwide and frequently occurs in the elderly population. However, there was limited regarding the clinical profiles of DLBCL patients over 70 years. We aim to summarize this population’s clinical features, treatment strategies and survival outcomes in China. Methods This multicenter retrospective study was conducted in China from Jan 2012 to July 2020 to investigate the clinical features and survival outcomes. 239 patients with DLBCL over 70 years underwent pretreatment evaluations, treatment, and follow-up at local hospitals. The primary endpoints of this study were the progression-free survival (PFS) rate and overall survival (OS) rate at two years. The secondary endpoints included median PFS and OS, 5-year PFS and OS rates, and adverse events during treatment. Results With a median follow-up of 50 months (range, 1-102 months), the 2-year PFS and OS rates were 53.0% and 65.5%, respectively. The median PFS and OS were 42.1 months and 96.4 months, respectively, and the 5-year PFS and OS rates were 44.7% and 56.1%, respectively. Hematological toxicities were the most common adverse effects in this study, accounting for 90.4%; and leukopenia was the most frequently observed ≥ grade 3 event. Moreover, we found that no rituximab-containing treatment and chemotherapy cycles < 6 were significantly associated with inferior survival. Furthermore, in the 70-80 years group, a reduced chemotherapy dose was associated with a remarkably shorter OS, as the 2-year OS rate was 74.4% in the full dose group compared to 67.1% for the decreased-dose group, p=0.044. Conclusion Our study presented the clinical profiles and survival outcomes of elderly patients with DLBCL in China. Treating these patients needs careful evaluation for the toxicities and benefits. Based on the prognosis model, like CGA, administering elderly patients with DLBCL is required in clinical practice.